2007
DOI: 10.1038/sj.mt.6300212
|View full text |Cite
|
Sign up to set email alerts
|

Replication-competent Adenovirus-mediated Suicide Gene Therapy with Radiation in a Preclinical Model of Pancreatic Cancer

Abstract: In preparation for a Phase I trial, we evaluated the efficacy and toxicity of replication-competent adenovirus-mediated suicide gene therapy in combination with radiation in a preclinical model of pancreatic cancer. Human MiaPaCa-2 and PANC-1 pancreatic adenocarcinoma cells were found to be sensitive to the oncolytic effects of the Ad5-yCD/mutTK(SR39)rep-ADP adenovirus and also to the cytotoxic effects of the yeast cytosine deaminase (yCD) and herpes simplex virus thymidine kinase (HSV-1 TK(SR39)) genes in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…[6][7][8][9] Intra-arterial injections of dl1520, in conjunction with total body irradiation (5 Gy), result in enhanced anti-tumor efficacy in p53 functional human malignant glioma xenograft models. 5 Moreover, Freytag et al 4 have shown that oncolytic Ad-mediated suicide gene therapy augments the effectiveness of pancreatic radiotherapy without resulting in significant toxicity. Enhanced antitumor efficacy has also been shown in combination studies using Ad5ÀD24RGD (Rb-binding mutant oncolytic Ad with an RGD (arginyl-glycyl-aspartic acid) motif in the HI-loop), CV706 (PSA (prostate-stimulating antigen)-selective oncolytic Ad) and Ad5-CD/TKrep Ads (oncolytic Ad containing a cytosine deaminase and herpes simplex virus thymidine kinase fusion gene).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Intra-arterial injections of dl1520, in conjunction with total body irradiation (5 Gy), result in enhanced anti-tumor efficacy in p53 functional human malignant glioma xenograft models. 5 Moreover, Freytag et al 4 have shown that oncolytic Ad-mediated suicide gene therapy augments the effectiveness of pancreatic radiotherapy without resulting in significant toxicity. Enhanced antitumor efficacy has also been shown in combination studies using Ad5ÀD24RGD (Rb-binding mutant oncolytic Ad with an RGD (arginyl-glycyl-aspartic acid) motif in the HI-loop), CV706 (PSA (prostate-stimulating antigen)-selective oncolytic Ad) and Ad5-CD/TKrep Ads (oncolytic Ad containing a cytosine deaminase and herpes simplex virus thymidine kinase fusion gene).…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, a therapeutic regimen combining radiation with oncolytic Ad has shown some promise in controlling tumor cell growth. [2][3][4] An E1B 55 kDa-deleted oncolytic Ad, dl1520 (ONYX-015), has been shown to potentiate radiation therapy, 5 leading to several pre-clinical studies examining the value of combining these two modalities. [6][7][8][9] Intra-arterial injections of dl1520, in conjunction with total body irradiation (5 Gy), result in enhanced anti-tumor efficacy in p53 functional human malignant glioma xenograft models.…”
Section: Introductionmentioning
confidence: 99%
“…An E1B 55 kDa-deleted conditionally replicated adenovirus, ONYX-015, has been observed to potentiate radiation therapy, resulting in several pre-clinical studies analyzing the value of combining the two treatments (12). Several specific types of oncolytic adenovirus administered in combination with radiotherapy have been observed to exhibit greater antitumor effects than treatment with either therapy alone (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…In another study Freytag et al [47] explored the efficacy and toxicity of using a secondgeneration adenovirus (Ad5-yCD/mutTKsr39rep-ADP) for combining replication-competent adenovirus-mediated suicide gene therapy with radiation therapy in an experimental dog model of pancreatic cancer. The authors demonstrated the feasibility of monitoring HSV1-sr39tk gene expression using [ 18 F]FHBG during the therapeutic trial.…”
Section: Hsv1-tk and Reporter Gene Expressionmentioning
confidence: 99%
“…Noninvasive and quantitative imaging of transgene expression using either wild type or mutant HSV1-tk-based reporter gene systems has been evaluated in preclinical models for monitoring adenoviral gene delivery [47], oncolytic herpesvirus therapy [48], adoptive cellbased therapies [49], and antitumor immune response [50], to name a few. The use of a reporter gene strategy is particularly useful to determine the spatiotemporal distribution and magnitude of expression of transgene expression to direct gene therapy in vivo.…”
Section: Hsv1-tk and Reporter Gene Expressionmentioning
confidence: 99%